Effect of temperature on development and population growth of Acarophenax lacunatus (Cross and Krantz) (Prostigmata: Acarophenacidae) on Rhyzopertha dominica (F.) (Coleoptera: Bostrichidae) - Faroni, L. R. D. A.; Guedes, R. N. C.; Matioli, A. L. (Taylor & Francis, 2001)
The parasitic mite Acarophenax lacunatus kills the eggs upon which it feeds and seems to have potential as a biological control agent of stored grain pests. The lack of biological studies on this mite species led to the present study carried out in laboratory conditions at eight different temperatures (ranging from 20 to 41°C) and 60% relative humidity using Rhyzopertha dominica as host. The higher the temperature, the faster: (1) the attachment of female mites to the host egg (varying from 1 to 5 h); (2) the increase in body size of physogastric females (about twice faster at 40°C than at 20°C); and (3) the generation time (ranging from 40 to 220 h). In addition, the higher the temperature, the shorter the maximum female longevity (ranging from about 75 to 300 h). The two estimated temperature thresholds for development of A. lacunatus on R. dominica were 18 and 40°C. The average number of female and male offspring per gravid mite were 12.8 and 1.0, respectively, with sex ratios (females/total) ranging from 0.91 to 0.94 (maximum at 30°C). The net reproductive rate and intrinsic rate of increase also presented maximum values at 30°C (12.1 and 0.04, respectively).
Keywords: Biological control; Biology; Lesser grain borer; Parasitic mite; air temperature; biocontrol agent; body size; egg; female; food storage; grain; host; humidity; parasitism; pest control; progeny; reproductive development; sex ratio; grain crop; mite; temperature effect